Impact of two COVID-19 lockdowns on HbA1c levels in patients with type 2 diabetes and associations with patient characteristics: a multicentre, observational cohort study over three years - Schäfer, Ingmar; Tajdar, Daniel; Walther, Laura; Bittner, Lasse; Lühmann, Dagmar; Scherer, Martin (Frontiers in Public Health, 2024)
Introduction: Glycemic effects of COVID-19 lockdowns on patients with type 2 diabetes (T2D) are controversial. In this long-term observation, we aimed (1) to analyze changes in HbA1c levels during lockdowns in Germany, and (2) to investigate whether diabetes medication, comorbidities, and sociodemographic data influenced these changes. Materials and methods: This cohort study observed 1,089 patients aged ≥18 years over the years 2019 to 2021. Patients were recruited from 14 physicians specialized on diabetes. As dependent variable, 7,987 HbA1c values were analyzed by multivariable linear regression adjusted for random effects of physicians and patients. Results: Patients had a median age of 68 (60/76) years and 623 (57.2%) were male. Before the pandemic, median HbA1c level (in %) was 6.9 (6.3/7.7). Average HbA1c level increased during first lockdown (0.21,0.11/0.31,p<0.001), after first lockdown (0.23,0.18/0.28,p<0.001), during second lockdown (0.40,0.33/0.47,p<0.001) and after second lockdown (0.27,0.18/0.36,p<0.001). The increase of HbA1c levels was more pronounced in male patients (0.08,0.01/0.15,p=0.019), if patients did not have German as native language (0.12,0.01/0.23,p=0.041) and if they were widowed (0.19,0.05/0.32,p=0.008). End organ damages (0.12,0.01/0.23,p=0.039), atherosclerotic cardiovascular disease (ASCVD; 0.23,0.10/0.36,p=0.001) and cardiovascular events (0.25,0.10/0.40,p=0.001) as well as oral medication (0.09,0.03/0.15,p=0.002), intermediate- or long-acting insulins (0.24,0.16/0.32,p<0.001), and fast-acting or mixed insulins (0.30,0.23/0.36,p<0.001) were also related to a greater increase in HbA1c levels. Conclusion: Both lockdowns resulted in a significant increase in HbA1c levels. In particular, patients with ASCVD, cardiovascular events, and insulin therapy appear to be at risk for worsening glycemic control in crisis and thus require special medical attention. Study registration: ClinicalTrials.gov (NCT04821921)